2012
DOI: 10.1371/journal.pone.0032737
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Mitochondrial Dynamics and Metabolomic Signatures of Evolving Energetic Stress in Mouse Models of Familial Alzheimer's Disease

Abstract: BackgroundThe identification of early mechanisms underlying Alzheimer's Disease (AD) and associated biomarkers could advance development of new therapies and improve monitoring and predicting of AD progression. Mitochondrial dysfunction has been suggested to underlie AD pathophysiology, however, no comprehensive study exists that evaluates the effect of different familial AD (FAD) mutations on mitochondrial function, dynamics, and brain energetics.Methods and FindingsWe characterized early mitochondrial dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
212
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(235 citation statements)
references
References 83 publications
(107 reference statements)
22
212
1
Order By: Relevance
“…Previous studies using in vivo proton magnetic resonance spectroscopy ( 1 H MRS) found decreases in N-acetylasparatate and glutamate, and an increase in myo-inositol concentrations in APP/PS1 mice (Chen et al, 2012;Marjanska et al, 2005). Glycolytic pathways involving the Kreb's cycle, and neurotransmitter and amino acid metabolism, were found to be significantly affected in APP/PS1 mouse brain (Trushina et al, 2012). Furthermore, 1 H NMR metabolomics studies found altered ascorbate, creatine, Îł-aminobutyric acid and NAA in APP/PS1 mouse brain, and altered acetate, citrate, glutamine and methionine in blood plasma (Graham et al, 2013b).…”
Section: Metabolomics Is the Scientific Investigation Of Chemical Promentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies using in vivo proton magnetic resonance spectroscopy ( 1 H MRS) found decreases in N-acetylasparatate and glutamate, and an increase in myo-inositol concentrations in APP/PS1 mice (Chen et al, 2012;Marjanska et al, 2005). Glycolytic pathways involving the Kreb's cycle, and neurotransmitter and amino acid metabolism, were found to be significantly affected in APP/PS1 mouse brain (Trushina et al, 2012). Furthermore, 1 H NMR metabolomics studies found altered ascorbate, creatine, Îł-aminobutyric acid and NAA in APP/PS1 mouse brain, and altered acetate, citrate, glutamine and methionine in blood plasma (Graham et al, 2013b).…”
Section: Metabolomics Is the Scientific Investigation Of Chemical Promentioning
confidence: 96%
“…It holds considerable potential as a discovery platform for identifying novel diagnostic biomarkers for AD but also many other neurodegenerative diseases. Metabolomics studies have previously been undertaken in APP/PS1 mice (Chen et al, 2012;GonzalezDominguez et al, 2015a;GonzĂĄlez-DomĂ­nguez et al, 2014;Graham et al, 2013b;Marjanska et al, 2005;Trushina et al, 2012;Yao et al, 2009), however, the majority of these studies (including our own (Graham et al, 2013b)) suffer from limitations commonly befalling many metabolomics investigations conducted to date. The current study was designed having noted earlier approaches to undertake a more robust metabolomics evaluation of this important model of AD.…”
Section: Metabolomics Is the Scientific Investigation Of Chemical Promentioning
confidence: 99%
“…Mitochondrial dysfunction has been suggested to underlie AD pathophysiology [111]. Deposition of heavy metals and alteration of the mitochondrial functionality are some of the facts and effects of oxidative stress observed in AD process [112].…”
Section: Metabolomics and Ad In Csfmentioning
confidence: 99%
“…Trushina et al studied the mitochondrial dynamics and function (motility, distribution, ultrastructure, etc) in neurons and brain tissue of three transgenic mice models expressing mutant human APP (Tg2576), PS1 (M146L mice) and the double mutation APP/PS1 [111].…”
Section: Metabolomics and Ad In Post-mortem Brain Tissuementioning
confidence: 99%
See 1 more Smart Citation